Kumpulan Wang Simpanan Pekerja (KWSP Segamat) / Nur Ain Abdul Razak - Abdul Razak, Nur Ain (Faculty of Business and Management, 2023)
Industrial training is very important and compulsory for all students who are in the last semester. All students need to go through internship program for six months. As a last semester student of Office Systems (BA232), I need to find company that is related with my field. In this report, I will explain about my internship report for six months in the company that I had to work which is Kumpulan Wang Simpanan Pekerja (KWSP) at Segamat. I started my journey of internship on 1st March 2023 and will be end until 15th August 2023. During my internship, I will be under the supervision of Encik Azmawi bin Omar. In this company, I get to work in Services Department. In this report, I will explain about the company’s profile which include background of company, vision, mission, organization structure, student’s profile and the services or products of KWSP. I also explain about the training's reflection, the details of roles and responsibilities during internship and also swot analysis of KWSP company. Swot analysis is very important to analyze and recognize the company’s problem so that, company can take an appropriate step to resolve the problem and improve to be better. I have identified a few strengths, weaknesses, opportunities and threats of KWSP. I will explain the details in the swot analysis page. From my observation and findings, all swot analysis will be discussed and will be provide with recommendation for each swot. I will try to find a best solution or idea to improve the strengths, weaknesses, opportunities and threats. In a nutshell, I have learned a lot of knowledge and also gain a lot of experience throughout my internship journey. It is quite interesting and beneficial for my future. I have learned on how to work in a real situation. I also manage to be an independent person and learn how to survive during my internship. Hence, I had a great opportunity to work with services department people, it was comfort me to develop the communication, punctuality, commitment, talents and teamwork abilities. It is a valuable memory that I will keep in my mind and use for the future.